Enhancing Civic Mathematics Knowledge of Students Through PMRI Approach - Djam'an, Nurwati (Cita konsultindo, 2025)
Critical mathematical thinking is inevitable in becoming a concerned citizen and an active part of modern society. Such knowledge would improve understanding of the learning mathematics process and suggest better teaching methods, which is especially crucial for teaching civic knowledge. This research develops mathematics learning tools and investigates the effectiveness of implementing the Indonesian Realistic Mathematics Learning (PMRI) approach based on civic mathematics in grade VII of Senior High School in the odd semester of 2024/2025. The learning tools in this study allow students to see issues in social contexts and relate them to mathematics. This study involved one participant teacher and 25 student participants. Action research and mixed methods were used in this research. This approach has allowed teachers and students to increase their activities in learning mathematics and improving students’ mathematics achievement. Before implementing the approach, students completed only nine students or 36%; in the first cycle, the student's achievement increased to 16 students or 64%; in the second cycle, 23 students, or 88%, had met the completeness. Also, by designing materials that link mathematics education with citizenship education, based on an interdisciplinary basis, this research provides a new important example of the transfer of mathematical roles. In this study, mathematics education is allocated to its role in efforts to build a democratic society.